Effective Motivational Factors: A Comparison Between Employees in China and the UK - Patel, Saisha (2017)
Differences in culture, political systems, economies and management system have led to different employees in different nations requiring a diverse set of job attributes and preferences. Hence, employees may have dissimilarities in the motivational factors that are effective at motivating them to a higher degree. This research aims to investigate the key differences between effective motivational factors for employees in China and the UK. The research uses a mixed-method approach of questionnaires and interviews to collect data from participants in Greater London and Ningbo. Descriptive statistical analysis such as t-tests are conducted using SPSS to answer the research questions. The present research found no significant difference between the effect of extrinsic motivational factors on employees from China and the UK. Whereas, a significant difference has been identified between the effect of intrinsic motivation factors on employees from China and the UK. Employees from the UK find intrinsic motivational factors more effective than employees from China. Yet, when considering each factor individually, there is differences in the what the most effective motivational factors are for each population. The most effective motivational factors on employees in the UK are; interesting job, desirable work environment and a sense of challenge and achievement. Whilst in China, the most effective motivation factors on employees are; good pay, good supervisors and good welfare package. It is believed that these findings can assist managers in China and the UK, to effectively motivate their employees. The practical implications can also be applied to organisations located in other parts of the world which have British and Chinese employees.